Dinâmicas de poder dos EUA por um Iraque pós-Saddam: a articulação entre o governo norte-americano e as elites do poder iraquiano na década de 1990 - Amaral, Rodrigo Augusto Duarte (2022)
Between May 2003 and July 2004, the United States of America together with Great Britain was the Provisional Authority of Iraq, as recognized by United Nations Security Council Resolution 1483. Since then, the US has invested trillions of dollars in aid and military spending in the country, one of the biggest financial outlays in its history. Even with the transfer of power to the Iraqis in July 2004, the US continued to influence Iraqi conditions in terms of governance, security, foreign policy (diplomacy) and economic guidelines, without leaving behind the reconstruction mechanism and the current military occupation. Therefore, this thesis proposes the following research question: What mechanisms ensured the permanence of the US liberal agenda in Iraq after the 2004 transfer of power? Since the invasion, the Americans and British have relied on the support of certain Iraqi power elites to back their actions. These elites were made up of political groups in opposition to the Baath party (of Saddam Hussein) that had been in dialogue with Western powers since the 1990s. They participated in the reconstruction process in 2003 and have subsequently formed the country's governing body since the establishment of the new Iraqi constitution of 2005.In this way, it is hypothesized that the articulation between the US government and these antiBaahtist Iraqi elites between 1990 and 2003 was a determining factor for the US permanence in Iraq after the transfer of power, which later culminated in an intense US- Iraq ever since. Through a qualitative analysis of the social networks of anti-Baathist Iraqi elites, this thesis aims to demonstrate who these Iraqi opposition leaders are and how they acted as US supporters in Iraq since 1990. We will seek to identify the articulation of these non-governing Iraqi elites and the US government within a broader framework of US international intrusive actions that will be categorized in this work. Finally, we understand that this intervention process to transform Iraq's political and economic structures fits within a scope of US hegemonic action in the Middle East, based on liberal normative principles such as democratic promotion and economic liberalization